Pseudomonas otitidis: discovery, mechanisms and potential biotechnological applications - Jianfeng, Gao; Mohamad, Rosfarizan; Halim, Murni; Mohamed, Mohd (Istanbul University Press, 2023)
Pseudomonas otitidis is a species of Pseudomonas bacteria discovered in the early 2000s and has been studied systematically by many researchers. P. otitidis has been isolated from various infected parts of diseases, such as otitis, recurrent pneumonia, necrotizing fasciitis, peritonitis, foot cleft, or burns. It has been found to produce a variety of enzymes to decompose pollutants in the environment such as petroleum, polycyclic aromatic hydrocarbons, dyes, sodium dodecyl sulfate, zearalenone, etc. Furthermore,it can produce some ingredients for application in agriculture and health industries such as digestive enzymes, melanin, and L-asparaginase. Some scholars used P. otitidis as a model organism to investigate environmental degradation, biobattery, plant growth promotion, and biodegradable plastic polyhydroxyalkanoate production. The biofilm of P. otitidis consists of rhamnolipid. The research has provided the basis to produce rhamnolipid and the effective removal methods of P. otitidis. P. otitidis is prone to resistance to lactam antibiotics, and its resistance is caused by its unique metallo-β-lactamase, a polyoxometalate enzyme. In other words, P. otitidis is a very interesting bacterium candidate to be used in different research fields. Hence, in this paper, the discovery, mechanisms, and potential biotechnological applications of P. otitidis are described.